PEMEROLEHAN BAHASA ANAK (STUDI KASUS TERHADAP PEMEROLEHAN BAHASA ANAK USIA DINI) - Sahril Nfn (MEDAN MAKNA: Jurnal Ilmu Kebahasaan dan Kesastraan, 2019)
A child does not suddenly have the first grammar in the brain, complete with all the rules. First language was obtained with several stages, and each subsequent stage nearer the grammar of adult language. This study aims to determine the system language acquisition of children aged 2.3 years to 2.6 years of age, especially those that include phonology, morphology, and syntax. The theory used in this study is the theory of language acquisition. The findings of the study, namely the age of 2.5 years, a normal child can already pronounce phonemes, and words are limited. At age 2.3 to 2.5 years, the words that were produced have started to grow and start of nouns and verbs. At the age of 2.5 years has been able to assemble simple words.